2010
DOI: 10.1111/j.1749-7345.2009.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Twin Screw Extrusion of DDGS‐Based Aquaculture Feeds1

Abstract: Six isocaloric (3.65 kcal/g), isonitrogenous (35% dry‐basis [db] protein), ingredient blends were prepared with 0, 17.5, 20, 22.5, 25, and 27.5% distiller's dried grains with solubles (DDGS) and other ingredients (soybean meal, corn, fish meal, whey, soybean oil, vitamin and mineral mix). The blends were moisture balanced to 15% db, then extruded in a twin screw extruder using a 2 mm die at 190 rpm, and a 3 mm die at 348 rpm. Analyses of the extrudates included moisture content, expansion ratio, unit density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Currently, the beef, dairy, swine, and poultry feed industries are the largest consumers of DDGS (Shurson and Noll 2005;RFA 2011a). Studies have also explored the use of DDGS in aquaculture feeds Schaeffer et al 2009;Kannadhason et al 2010). A very small percentage of the DDGS market includes deicers, cat litter, "lick barrels," and worm food (Bothast and Schlicher 2005).…”
mentioning
confidence: 99%
“…Currently, the beef, dairy, swine, and poultry feed industries are the largest consumers of DDGS (Shurson and Noll 2005;RFA 2011a). Studies have also explored the use of DDGS in aquaculture feeds Schaeffer et al 2009;Kannadhason et al 2010). A very small percentage of the DDGS market includes deicers, cat litter, "lick barrels," and worm food (Bothast and Schlicher 2005).…”
mentioning
confidence: 99%
“…Previous studies have shown that the amount of extrudate produced per unit time is impacted by screw speed, die geometry, shear rate, diet formulation (such as DDGS level), moisture content, and the viscosity of the dough melt (Chevanan et al, 2008;Kannadhason et al, 2010). In this study, except for screw speed, none of the independent variables had significant effects on MFR for the main effects, which again was related to the high standard deviations observed in the data.…”
Section: Mass Flow Ratementioning
confidence: 48%
“…Previous studies have shown that extrudate MC increased with higher DDGS levels (Ayadi et al, 2011b;Kannadhason et al, 2010) as well as the MC of the raw blends . In this study, extrudate MC decreased significantly (by 8.8%) when DDGS content of the blends increased from 20 to 30%, whereas MC did not show significant effects when increasing DDGS level from 30 to 40%.…”
Section: Moisture Contentmentioning
confidence: 87%
“…Simons found that as extruder screw speed increases, water activity decreases (Simons et al, 2012). Color of the extrudate indicates, to some extent, the nutritional quality of the product (Kannadhason et al, 2010), as darker colors can indicate protein degradation. The mass flow rate quantifies the processing performance of the extruder (Ayadi et al, 2011c).…”
Section: Introductionmentioning
confidence: 99%
“…It plays a major role in many third world countries because it produces relatively higher income, better nutrition, and better employment opportunities (Kannadhason et al, 2008). Nutritional feed for aquaculture is costly, and the feed cost is generally 30% to 60% of total operational costs (Kannadhason et al, 2009(Kannadhason et al, , 2010, both due to raw ingredient costs as well as processing costs. Because feed is so expensive, it is difficult to provide the fish appropriate nutrients they need to thrive.…”
Section: Introductionmentioning
confidence: 99%